Human Salivary Gland Stem Cells Functionally Restore Radiation Damaged Salivary Glands. (21st March 2016) - Pringle, Sarah; Maimets, Martti; van der Zwaag, Marianne; Stokman, Monique A.; van Gosliga, Djoke; Zwart, Erik; Witjes, Max J.H.; de Haan, Gerald; van Os, Ronald; Coppes, Rob P.
Abstract: Adult stem cells are often touted as therapeutic agents in the regenerative medicine field, however data detailing both the engraftment and functional capabilities of solid tissue derived human adult epithelial stem cells is scarce. Here we show the isolation of adult human salivary gland (SG) stem/progenitor cells and demonstrate at the single cell level in vitro self-renewal and differentiation into multilineage organoids. We also show in vivo functionality, long-term engraftment, and functional restoration in a xenotransplantation model. Indeed, transplanted human salisphere-derived cells restored saliva production and greatly improved the regenerative potential of irradiated SGs. Further selection for c-Kit expression enriched for cells with enhanced regenerative potencies. Interestingly, interaction of transplanted cells with the recipient SG may also be involved in functional recovery. Thus, we show for the first time that salispheres cultured from human SGs contain stem/progenitor cells capable of self-renewal and differentiation and rescue of saliva production. Our study underpins the therapeutic promise of salisphere cell therapy for the treatment of xerostomia. Abstract : Human salivary gland stem cells cultured as salispheres are able to self-renew and differentiate from single cells into salivary gland organoids. When xeno-transplanted into an animal model of radiation-induced hyposalivation, human salivary gland stem cells rescue saliva production.